Digging, damming or diverting? small-scale irrigation in the Blue Nile basin, Ethiopia - Eguavoen, I.; Derib, S.D.; Deneke, T.T.; McCartney, Matthew P.; Otto A; Billa S (2011)
The diversity of small‐scale irrigation on the Fogera plains, in the Ethiopian Blue Nile river basin, includes small dams, hand‐dug wells, ponds and river diversion systems. These facilities, however, receive little political attention in negotiations over Nile resources, which focus primarily on large dams. Nevertheless, they are important in relation to their impact on local livelihoods, as well as their potential to contribute to adaptive capacity in the light of anticipated climate change. The diversity of irrigation infrastructure is partly a consequence of the topographic heterogeneity of the plains, as well as a range of other biophysical factors. Communities within the region cope with similar social‐political conditions, the same administrative framework and similar access to markets, yet facilities are still acquired, used and managed differently. Production systems as well as the social dynamics accompanying them are far from homogeneous, though, which calls for critical evaluation, especially as small scale irrigation is managed by beneficiaries; a policy paradigm just starting to be implemented for large dams in Ethiopia. The article also discusses the impact of large dams on the hydrological regime of the plains, as well as the possible impact of anticipated climate change.